Sign Language Is Not Just Hand Gestures: The Linguistic Complexity of BISINDO and Its Role in Deaf Inclusion - Nurasia Natsir; Muhammad Nur Iman (International Journal of Educational Research, 2026)
Indonesian Sign Language (Bahasa Isyarat Indonesia, BISINDO) is often misunderstood as merely a gestural or simplified form of communication, undermining its linguistic sophistication and contributing to barriers to deaf inclusion in Indonesia. Approximately 2.6 million deaf individuals in the country rely on BISINDO as their primary language. This study explores the linguistic complexity of BISINDO, documenting its phonological, morphological, syntactic, and semantic systems. Using a mixed-methods approach, we analyzed 150 hours of BISINDO conversations from 80 deaf signers, conducted experimental studies on phonological distinctions and syntactic complexity, and performed ethnographic fieldwork in deaf communities and schools. Comparative analysis with American Sign Language (ASL) was also conducted. Our findings demonstrate that BISINDO is a fully developed natural language, with 45 handshapes, 18 locations, 23 movements, and 4 orientations in its phonological system. It shows productive morphological processes, flexible word order, and rich semantics, including idioms and metaphors. However, there are significant barriers to inclusion: 68% of deaf students lack qualified BISINDO teachers, and 84% of public services lack sign language interpreters. Furthermore, 72% of hearing Indonesians still do not recognize BISINDO as a legitimate language. Deaf community organizations, however, report BISINDO as central to their identity. The study highlights the need for policy reforms, including BISINDO recognition as an official language, qualified interpreters, bilingual deaf education, and public awareness campaigns to combat misconceptions.